Understanding Educational Management in The Context of Environmental Protection for Madrasah Application - Raudah Raudah; Achmad Hidir; Muhammad Nor; Sa'adah Erliani (Program Studi Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2021)
Environmental protection education in Indonesia must get the attention of all parties, especially the government and its staff, because healthy environmental resources must be pursued, not surrendered, let alone let them be damaged and extinct. For this reason, it takes the government's seriousness as the maker and implementer of policy regulations through education on environmental protection that is healthy and free from irresponsible human intervention. For this purpose, we have reviewed more than a hundred international publications that have discussed environmental safety issues through application to school education in various contexts to become a model for application in Madrasah schools in Indonesia. We reviewed papers published between 2010 and 2021 as sources of scientific data and other research sources to prove this assumption. We chose a systematic review method to understand the main problem through coding systems, data evaluation, in-depth analysis, and interpretation before obtaining findings to answer environmental research problems, education, and realities of practice in the field. Based on the data found and the discussion results, we understand the relevance between government policies on government regulations and the content and behavior taught in madrasas and industry on attitudes and behavior and sanctions on the preservation and sustainability of environmental protection.